Cardiac Myosin-binding Protein-C as a Biomarker in the Early Diagnosis of Acute Coronary Syndrome and Differentiation of Its Types - Ali Abdul Rasool Hussein; Abdulkareem Hamadi Issa; Abbas Naji Muslem Al Shareeifi (Mustansiriya Medical Journal)
Background: Coronary heart disease (CHD) is primarily caused by atherosclerotic lesions within the intima of coronary arteries and acute coronary syndrome (ACS) is the main acute clinical manifestation of CHD. The ACS is manifested in one of three subtypes and it is the leading cause of mortality worldwide. The three subtypes of ACS include: acute myocardial infarction (MI) with the electrocardiogram (ECG) presenting ST-segment elevation (STEMI), MI with no ST-segment elevation on ECG (NSTEMI), and the third subtype is unstable angina (UA). The early diagnosis of is important in decreasing morbidity and mortality in ACS patients. Objective: To investigate the role of serum level of cardiac myosin-binding protein-C (cMyC), compared with high-sensitivity cardiac troponin-I (hsCTn-I) in the early diagnosis of ACS and differentiation of its subtypes. Materials and Methods: One hundred and twenty patients (72 males and 48 females), aged ≥30 years selected from those who were admitted to emergency department (ED) of Al-Yarmouk teaching hospital and diagnosed with ACS by cardiologists. The duration between the onset of chest pain and admission to ED should not exceed 3 h in any cohort. Apparenty healthy subjects as controls group for the study were recruited from those who had no current illness, particularly CHD, no other systemic disease and each had a normal ECG. For each study subject, cMybp-C and hsCT-I serum levels on admission were measured using the enzyme-linked immunosorbent assay kits. For each ACS patient, serum level of hsCTn-I level was measured 3 h after admission. Results: The comparison of cMybp-C levels among study groups revealed an overall significant difference and on paired comparison of study groups, the cMybp-C mean level was significantly higher in each ACS subgroup than in controls group (P < 0.001), except in UA subgroup versus controls group. The cMybp-C levels showed a significant positive correlation with hsCT-I levels on admission in STEMI and NSTEMI subgroups but not in UA subgroup. The cMybp-C levels also showed a significant positive correlation with hscT-I levels 3 h after admission in STEMI and NSTEMI subgroups but not in UA subgroup. On receiver operating characteristic curve analysis, the cMybp-C level had a better diagnostic accuracy than hscTn-I on admission in differentiation of patients with “STEMI or NSTEMI” from those with UA or from controls. Conclusion: Serum cMybp-C mean level is significantly higher in ACS patients with STEMI and NSTEMI than in controls and the increase was more significant than hsCTn-I mean level on admission, so it could help the early diagnosis of ACS patients. The serum levels of cMybp-C also had a better diagnostic accuracy than hsCTn-I on admission in differentiation of ACS patients with STEMI or NSTEMI from those with UA or from controls.